Sistemas de ganado lechero en Kenia: Contexto económico y perspectivas para las nuevas tecnologías forrajeras - Junca Paredes, Jhon Jairo; Flórez, Fernando; Enciso, Karen; Hernández, Luis Miguel; Triana Ángel, Natalia; Burkart, Stefan (Bioversity International and the International Center for Tropical Agriculture, 2023)
According to the World Bank, Kenya’s GDP growth was 7.5% and its unemployment rate 5.7% in 2021, evidencing good economic performance. But when consulting social data, the prevalence of malnutrition has grown since 2014 and reached 27% by 2020. Kenya is also affected by adverse climatic conditions. In this context, dairy production has an important role: it is an economic driver and a provider of quality food, but also subject to climate change. With 5,112,340 dairy cattle in 2020, Kenya has one of the largest dairy cattle herds in Africa. Small-scale production is predominant and cut-and-carry forage systems prevail. As a response, research focused on the development of forages with higher productivity, resistance to pests and diseases, and better nutritional quality. The experiences made with forage hybrids in the country are positive, for example with Urochloa hybrid cv. Mulato II, but adoption levels remain low. Against this background, this study aims at estimating the potential market for new forage hybrids adapted to the Kenyan environment. With information on the dairy cattle herd, geographic information systems, and cluster analysis, the potential hectares of new interspecific Urochloa and potential Megathyrsus maximus hybrids are estimated. Results show a potential area for new interspecific Urochloa hybrids of 75,573 hectares, and of 78,372 hectares for potential hybrids of Megathyrsus maximus, with annual commercial values of around US$ 15 million each. Despite this potential, technological changes at the farm level are subject to e.g., infrastructure and market restrictions, weaknesses in extension programs, and access to financing. It is thus required to focus on both the development of a forage hybrid seed sector and strengthening these macro-conditions. Only then adoption will happen and come along with livelihood benefits and contribute to increasing food security.